Configuration of gRPC Java with envoy proxy for web clients - Benarous, Mohamed Okba; Betaimi, Oussama Abderaouf; Ben Saad, Mohamed Lahcen (Université Amar Telidji - Laghouat - Département d'informatique, 2019)
GRPC is used in last mile of computing in mobile and web client since it can generate libraries for various of systems, It is modern, fast and efficient framework, build on top of HTTP/2, and works across languages and platforms. There is also work underway to develop a JS library for use in browsers. GRPC is Remote Procedure Call (RPC) system. It makes the microservices talk to each other at light-speed. gRPC is the best choice for the creation of client-server and browser-based web applications. Beyond that, we can find gRPC almost anywhere you have two computers communicating over a network: Microservices, Client-Server Applications, Integrations and APIS, Browser-based Web Applications. In web GRPC, the developers or the users faced some issues with the configuration, maintenance and managing of the proxy (envoy). In this thesis, we introduce to gRPC and explain how it compares and contrasts with similar technologies, then we explain Protocol Buffers, a key technology for using gRPC. In the end, we focus on gRPC web proxy and its issues and we provide some possible solutions.